Cement augmentation of hip implants in osteoporotic bone: How much cement is needed and where should it go?. Issue 3 (20th November 2013) - Sermon, A.; Hofmann‐Fliri, L.; Richards, R.G.; Flamaing, J.; Windolf, M.
ABSTRACT Several studies proved the beneficial effect of cement augmentation of proximal femoral nail antirotation (PFNA) blades on implant purchase in osteoporotic bone. We investigated the effect of different localizations and amounts of bone cement. Polyurethane foam specimens were instrumented with a PFNA blade and subsequently augmented with PMMA bone cement. Eight study groups were formed based on localization and amount of cement volume related to the blade. All specimens underwent cyclic loading with physiological orientation of the force vector until construct failure. Foam groups were compared between each other and to a cadaveric control group. The experiments revealed a significant dependency of implant purchase on localization and amount of cement. Biomechanically favorable cement positions were found at the implant tip and at the cranial side. However, none of the tested augmentation patterns performed significantly inferior to the cadaveric benchmark. These findings will allow surgeons to further reduce the amount of injected PMMA, decreasing the risk of cement leakage or cartilage damage. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:362–368, 2014.